New Graduate Nurses' Clinical Competence, Clinical Stress, and Intention to Leave: A Longitudinal Study in Taiwan. (25th December 2013) - Cheng, Ching-Yu; Tsai, Hsiu-Min; Chang, Chia-Hao; Liou, Shwu-Ru
Abstract : This longitudinal research study aimed to develop a pregraduation clinical training program for nursing students before graduation and evaluate its effect on students' self-perceived clinical competence, clinical stress, and intention to leave current job. A sample of 198 students returned the questionnaires before and after the program. They were followed up at 3, 6, and 12 months after graduation. Results showed that posttest clinical competence was significantly higher than pretest competence, positively related to clinical competence at 3 and 12 months, and negatively related to clinical stress at 3 months. The clinical competence at 3 months was positively related to clinical competence at 6 and 12 months, and clinical competence at 6 months was related to intention to leave at 12 months. Intention to leave at 6 months was positively related to intention to leave at 3 and 12 months. Clinical stress at 3 months was positively related to clinical stress at 6 and 12 months, but not related to intention to leave at any time points. The training program improved students' clinical competence. The stressful time that was correlated with new graduate nurses' intention to leave their job was between the sixth and twelfth months after employment.